STRATEGI GURU DALAM PEMBIASAAN TOILET TRAINING UNTUK ANAK USIA 4-5 TAHUN - Farantika, Dessy (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
Toilet training is a fundamental skill that is essential to instill from an early age because it plays a role in fostering independence, discipline, and responsibility in children. This study aims to analyze teacher strategies in promoting toilet training at Al Hidayah Tangkil 2 Kindergarten. A qualitative approach was used with a case study method. Data were collected through observation, teacher interviews, and activity documentation. Interview results were transcribed for thematic analysis, while observation data were recorded using a systematically compiled instrument throughout the learning activities. The findings indicate that the toilet training strategy was implemented in a structured and consistent manner. Teachers taught toilet etiquette according to religious guidance, trained children to queue, and instilled responsibility for personal belongings. The role of teachers was not only as facilitators but also as role models through direct practice and continuous communication. Obstacles that emerged included differences in home-school habits and limited parental understanding. Nevertheless, the strategy remained effective due to collaboration between educators. Practically, this study contributes to early childhood education teachers in designing consistent toilet training practices, based on religious values, and appropriate to children's developmental stages. For Islamic educational institutions, the results of this study can be used as a reference in developing more systematic habituation programs, involving parents, and strengthening the integration between aspects of personal hygiene and the formation of children's character. Keywords: the role of the teacher; toilet training; habituation